Structure, Dielectric, and Electrical Characterization of 0.9(Bi0.5Na0.5TiO3) – 0.1(Bi0.5Sr0.25TiO3) (BNT-BST) Solid Solution for Capacitor Applications - Aryal, Ram Prasad; Bhattarai, Binod Kumar (Journal of Advanced College of Engineering and Management, 2025)
Eco-friendly 0.9(Bi0.5Na0.5TiO3) - 0.1(Bi0.5Sr0.25TiO3) (BNT-BST) ceramics were synthesized via the solid-state reaction method. Structural, dielectric, and electrical properties were systematically studied. Rietveld refinement confirmed a pure rhombohedral perovskite structure with R3c symmetry. The dielectric constant peaked at 3456 @1kHz with a high transition temperature 303ºC. Two dielectric relaxations near 110ºC and 300ºC are attributed to R3c and p4bm PNRs. The dielectric peaks diminished with increasing frequency. Impedance and conductivity analysis indicated NTCR-type semiconducting behavior. Jonshcer’s law and frequency exponent trends suggest a conduction mechanism governed by the CBH model. Lastly, the modulus formalism further confirms that the electrical relaxation in the studied sample purely depends on the thermal agitation, as proposed initially by the impedance formalism. The poly-dispersive dielectric behavior is associated with various conduction mechanisms contributed by charge carriers/polarons with short/long-range displacement. The distinctive activation energies estimated from the multifaceted analyses depict that the overall electrical behavior is equally influenced by grains and grain boundaries. This analysis explores the wider applications of modified BNT-based ceramics in the field of electroceramics.